2014
DOI: 10.1016/j.sbspro.2014.11.089
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tax Agents in Sustaining the Malaysian Tax System

Abstract: In Malaysia, a self-assessment system has been implemented for all companies for more than a decade. The system necessitates corporate taxpayers to declare and calculate accurate sources of income, estimate income tax payable, keep records for audit purposes, and comprehend income tax legislation. In complying with these demands, many corporate taxpayers have to depend on the assistance of tax agents. Using survey data, this study aims to examine the role of tax agents in sustaining the SAS in Malaysia. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Furthermore, corporate taxpayers need to observe further tax requirements in SAS. The public ruling of SAS requires all taxpayers to file a correct annual tax return, keep sufficient records and documentations and to observe other tax related requirements (Abdul-Jabbar & Pope 2008a; Isa et al, 2014).…”
Section: Self-assessment Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, corporate taxpayers need to observe further tax requirements in SAS. The public ruling of SAS requires all taxpayers to file a correct annual tax return, keep sufficient records and documentations and to observe other tax related requirements (Abdul-Jabbar & Pope 2008a; Isa et al, 2014).…”
Section: Self-assessment Systemmentioning
confidence: 99%
“…This is particular true under the present self-assessment system (SAS) which has been implemented since 2001 by the Malaysian tax authorities. Under this system, it allows the taxpayers to compute their tax liability (Isa et al, 2014). According to Palil (2010), one of the major aims of introducing SAS in Malaysia is to collect taxes for the nation at minimum cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swistak (2016) suggests that specific penalties can increase tax compliance. As stated by Isa, Yussof, and Mohdali (2014), taxpayers are quite sensitive to tax auditing procedures and faced with a high audit probability, they feel pressured to comply (Hartl et al, 2015). Some authors identified ATE as playing an important role in tax compliance (Santos & Palma, 2013).…”
Section: Dimension 3: Ate Tax Compliancementioning
confidence: 99%
“…As people are constantly online and linked, they now expect tax payments to be part of their digital environment. Many taxpayers have to rely on tax agents to fulfil the compliance with tax obligations [4]. As such, this study aims to examine the readiness of tax agents to tackle the challenges and opportunities, including the acceptance of the digitalisation of tax administration in Malaysia.…”
Section: Introductionmentioning
confidence: 99%